2015
DOI: 10.1590/1414-431x20154387
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic resistance training decreases sympathetic tone in hypertensive ovariectomized rats

Abstract: The aim of this study was to investigate the effects of resistance exercise training on hemodynamics and cardiac autonomic control in ovariectomized spontaneously hypertensive rats. Female rats were divided into 4 groups: sedentary control (SC), sedentary hypertensive (SH), sedentary hypertensive ovariectomized (SHO), and resistance-trained hypertensive ovariectomized (RTHO). Resistance exercise training was performed on a vertical ladder (5 days/week, 8 weeks) at 40-60% maximal load. Direct arterial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Ovarian hormones deprivation induced an additional increase in AP in ovariectomized rats (HSO group), thus confirming previously published findings (17,19,36). Postmenopausal hypertension is probably associated with estrogen loss (43).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Ovarian hormones deprivation induced an additional increase in AP in ovariectomized rats (HSO group), thus confirming previously published findings (17,19,36). Postmenopausal hypertension is probably associated with estrogen loss (43).…”
Section: Discussionsupporting
confidence: 90%
“…Our group has previously reported that a reduction in mean AP was associated with increased vagal tonus in fructose-fed ovariectomized SHR after AT (35). On the other hand, it was also demonstrated that dynamic RT diminished AP in ovariectomized SHR due to a decrease in sympathetic tone (36). Therefore, in this study, we made a comparison between aerobic and RT, evidencing that both are able to induce blood pressure decrease, however, at different magnitudes and by different predominant mechanisms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Sendo assim, as adaptações periféricas responsáveis pela hipotensão no gênero feminino podem não ter sido atingidas com o exercício proposto neste estudo 24 . É interessante notar que apesar de não termos observado HPE nas ratas hipertensas no presente estudo, dados do nosso grupo demonstram que fêmeas hipertensas com prejuízo adicional da PA devido a privação de hormônios ovarianos, apresentam redução da PAM após treinamento físico resistido 25 . É importante ainda destacar que o fato de não haver agudamente aumento da PA no período pós exercício nas ratas hipertensas, sugere que o exercício físico resistido prescrito neste modelo não induziu aumento do risco cardiovascular.…”
Section: Discussionunclassified
“…Entretanto, um dado importante do presente estudo foi a redução da FC observada a partir do 15º minuto em relação aos primeiros cinco minutos da recuperação. Embora não tenha sido uma variável diretamente medida, a redução da FC observada nas fêmeas SHR pós exercício resistido dinâmico pode estar relacionada com diminuição do tônus simpático e/ou aumento do tônus parassimpático cardíaco 25 . Ao analisarmos a resposta do DP, observamos estreita semelhança com o comportamento da FC.…”
Section: Discussionunclassified